Stepfamilies - Allan, G. author. aut Link
XI, 197 p.
Keywords: Drawing on recent developments within the sociology of family life, this book examines family connection and solidarity within different stepfamily networks, focusing on relationships from a kinship perspective and using case studies of people's experiences to explore how family connection is constructed within different stepfamilies.